Making a Match before Tinder: Popular graffiti in Torrenueva (Ciudad Real, Spain) - Carrasco, Isabel (Street Art & Urban Creativity, 2022)
Traditionally, on the night of April 30th, marking the beginning of popular May celebrations, young men have gone out to write graffiti in the town of Torrenueva (Ciudad Real, Spain). This original graphic phenomenon is locally called “pintar los mayos” and consists of writing the word “MAYO” (“May” in Spanish) followed by the year of the execution (i.e., MAYO 98) on the façade of a girl's house as proof of interest and as an excuse to strike up a conversation. It is hard to confirm the origin of this custom with precision, but the tradition might date back from at least the 1940s. Today it's on the verge of disappearing; only one “mayo” was found in 2020 and none in 2021 or 2022. The ritual has evolved over the years in terms of purpose, location and medium and can be analyzed in the category of “love graffiti”.